Thermo-Mechanical Reliability of SOFC Stacks during Combined Long-Term Operation and Thermal Cycling. (2nd June 2015) - Greco, Fabio; Nakajo, Arata; Wuillemin, Zacharie; Van herle, Jan
Abstract : Thermo-mechanical issues in solid oxide fuel cells (SOFC) must be understood and overcome to meet the reliability standards for market implementation. This study presents a thermo-mechanical model of an SOFC-stack SRU. The analysis starts with the simulation of stack conditioning procedures, which aims at capturing the stresses during the stack components production and assembly. The simulated stresses after the initialisation sequence provide the initial stress-state for the simulation of stack operation, which consists in importing into FEA software the temperature profiles from thermo-electrochemical simulations. The study includes long-term steady-state operation in co-flow configuration, interrupted by thermal cycling. The SRU contact pressure was found to decrease significantly after a first thermal cycle to RT, after stack qualification. Thermal cycling after long-term operation worsens the extent of loss of contact pressure at room temperature. Similarly to the evolution of contact pressure, long-term operation increases the risks of sealant failure during thermal cycling.